Steam Supply Evaluation for Carbon Capture and Storage in a Subcritical Coal-Fired Power Plant - Hendrayawan, Veri; Raksajati, Anggit; Adisasmito, Sanggono; Juangsa, Firman Bagja (Universitas Negeri Malang, 2025)
The aim of this study is to analyze the implementation of carbon capture and storage (CCS) in coal-fired power plants (CFPP) in Indonesia by determining the reboiler energy demand through steam source analysis. The study uses a representative 3×330 MW subcritical coal-fired power plant (CFPP), with an emission intensity of 1.02 tCO₂/MWh and flue gas CO₂ concentration of 13.8%. CCS modeling shows the reboiler requires about 2.9×10⁹ kJ/h energy, supplied by steam extracted from the plant’s steam cycle. A steam cycle model was developed to evaluate the impact of steam extraction. Potential tapping points analyzed include main steam, cold reheat, intermediate-pressure (IP) extraction, low-pressure to intermediate-pressure LP-IP crossover, and low-pressure (LP) extraction. Main steam extraction with the highest energy content needs the lowest steam mass flow of 355 t/h but causes the highest energy penalty of 57% because of lost electricity production in HP and IP extraction. Cold reheat extraction requires moderate steam flow of 399 t/h and a penalty of 52% but risks overheating reheater tubes. The LP-IP crossover point needs the highest steam flow 414 t/h, yet achieves the lowest net energy penalty at 33.8% with minimal operational risk, making it the most favorable option for CCS integration.